The Effectiveness of KUR Holding Ultra Micro Financing as Capital for Development of Small and Medium Micro Enterprises - Majid, Jamaluddin; Nur, M Ilham; Rasulong, Ismail; Haliding, Safri (Jurnal Ekonomi Balance, 2024)
This analysis examines the effectiveness of KUR Holding Ultra Micro (UMi) financing as capital for developing MSMEs using the literature study method. Data was collected from relevant national journals published in the last five years, as well as other sources such as textbooks and scientific articles. The aim of this research is to obtain a theoretical basis that supports problem solving and reveals relevant theories. The research results show that KUR Holding UMi's financing is quite effective in helping MSMEs to develop. Timely disbursement of funds and loose installments really help debtors and reduce the level of bad credit. However, this research has limited information regarding the condition of MSMEs before receiving financing, so conclusions must be drawn with caution. Overall, the effectiveness of MSME credit shows good results with an increase in outstanding every year and a positive impact on communities receiving KUR funds. However, there are several important notes for BRI, Pegadaian and PNM who are responsible for this credit distribution.